Numerical investigation of flow field of a non-circular cylinder - Mohd Sajali, Muhammad Fahmi; Aabid, Abdul; Khan, Sher Afghan; Mehaboobali, Fharukh Ahmed Ghasi; Sulaeman, Erwin (Penerbit Akademia Baru, 2019)
The study of the base flow field or the flow field in the wake region is not accessible by using only a theoretical method; mostly this study has been done experimentally. The problem statement of this study is to know the effect of flow past of a non-circular cylinder on the drag. At high Reynolds number, the flow past a bluff body is characterized by a large wake zone. Therefore, drag reduction of the flow field is an interesting problem with a wide range of application. The present paper presents the numerical simulation of the flow field of a non-circular cylinder. The shielding effect of the square-plate front body on the flow field of drag reduction and the pressure distribution of a three-dimensional bluff body is simulated by using a numerical method. The results obtained from the simulation are compared with the experimental results. The results indicate that the side faces and the rear faces are subjected to low pressure, whereas the front face is experiencing high positive pressure. With this flow pattern, the pressure drag coefficient assumes a substantially significant value in the range of 1.0-1.42. Such a high value of drag coefficient is particularly valid for bluff bodies with noncircular cross-sections with sharp corners. © 2019 PENERBIT AKADEMIA BARU. All rights reserved.